The Influence of Non-Cash Transactions (Cashless) on Customer Convenience in Transacting at PT Pegadaian UPC Sudirman Pematang Siantar - Panjaitan, Santi Rohdearni; Panjaitan, Hadi; Sitanggang, Augustinus Suryadi; Barus, Ben Setiawan; Siburian, Maretta Selvana (ProBisnis : Jurnal Manajemen, 2025)
Pegadaian is a non-bank financial institution that officially has a permit to carry out its operational activities in the form of credit financing to the community in the form of distributing funds in relatively small or large amounts on the basis of pawn, as well as deposit services, appraisal services. The pawned goods must have economic value so that they can be used as an appraisal value by the pawnbroker. This study focuses on determining the effect of non-cash transactions (cashless) on customer convenience in transacting at PT Pegadaian UPC Sudirman, Pematangsiantar. The results of this study are that non-cash variables (cashless) have a positive and significant effect on customer convenience. This can be proven through the results of the t-test statistical test obtained a sig. value of 0.00 <0.05. The comparison of t-count 5.611> t-table 2.001. so it can be concluded that H0 is rejected and Ha is accepted, which means that cashless transactions (X) have a positive and significant influence on customer convenience (Y) of PT Pegadaian UPC Sudirman Pematangsiantar.